"Who Am I?" Learning Media in the Form of Augment Reality for Mapping Student’s Talent and Interest - Putri, Amallia; Yuniarni, Desni (Buletin Konseling Inovatif, 2025)
The guidance and counseling media occupy a crucial position in achieving service goals. The existence of media can enhance accessibility to services and facilitate the dissemination of information to students and counseling teachers. The long-term goal in the development of Learning Media in the Form of Augment Reality "Who Am I?" for the material of mapping talents and interests of Guidance and Counseling Study Program Students, Faculty of Teacher Training and Education Science, UNTAN, is to facilitate the integration of the media into the curriculum for guidance and counseling study program students during their teaching practice at school. The method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of 6 stages of development, namely concept, design, material collection, application development, application testing, and distribution. The research involved guidance and counseling students of the Faculty of Teacher Training and Education Science, UNTAN. The findings of this development research indicate that the learning media in the form of Augmented Reality "Who Am 1?" is an effective medium for the course of mapping the talents and interests of guidance and counseling students, as evidenced by the overall score of the validation questionnaire.